CONSUMER SATISFACTION ON BATH SOAP BRANDS - Dr Srinivas Gundarapu (International Journal of Advanced Science and Technology, 2020)
The Consumer mindset in the modern era is ever changing in terms of preferences and expectations.The companies are pushing themselves closer to the consumer mindset to attract them to prefer theirconcerned brands. Especially in the FMCG market in India is concerned, where number of brands arebeen promoted in Bath Soap brands, the satisfaction of consumer is what ultimately decides the fate ofthe survival and sustenance. In this scenario, the present study is an attempt to evaluate the satisfactionlevel of consumers on the basis of select dimensions of 3 select FMCG companies’ bath soaps. Further,the study will also make an attempt to understand the key factors influencing the consumer satisfactionon the bath soap brands using Factor Analysis.